Implementation of guidance and counseling activities for children with special needs at the kurnia gem center - Nasurdin, Mohamad Mustaqim Bin; Simamora, Irma Yusriani (Institute of Computer Science (IOCS), 2024)
The purpose of the study is solely to show an overview of how important the implementation of guidance and counseling to children with special needs from all types of diseases they face can be seen from the socio-cultural psychological aspects of the development of science and technology. One method used in this research is descriptive qualitative research, which involves describing the implementation of case studies in schools through interviews, documentation and observation. The most important thing to get for children with special needs is that counseling itself becomes the main need. This can be due to many things, such as psychological or emotional instability compared to the child's ability to socialize in a school or community setting, such as dealing with bullying or the use of social media, and how a child can interact with the world outside of their habits such as the use of technology or interaction with others. As a result of this study, we can find out about the impression of guidance and counseling to children with special needs under study. They can find out their strengths and weaknesses through the guidance and counseling process provided. These special needs children tend to feel comfortable with a positive environment in adapting to their needs and uniqueness in their environment.